Intermedial Theater - Reynolds, Bryan. author. aut Link
XVIII, 314 p. 30 illus., 26 illus. in color.
Keywords: This book explores relationships between intermedial theater, consciousness, memory, objects, subjectivity, and affect through productive engagement with the performance aesthetics, socio-cognitive theory, and critical methodology of transversal poetics alongside other leading philosophical approaches to performance. It offers the first sustained analysis of the work of Gilles Deleuze, Félix Guattari, Jean Baudrillard, and Friedrich Nietzsche in relation to the contemporary European theater of Jan Lauwers and Needcompany, Romeo Castellucci and Socìetas Raffaello Sanzio, Thomas Ostermeier, Rodrigo García and La Carnicería Teatro, and the Transversal Theater Company. It connects contemporary uses of objects, simulacra, and technologies in both posthumanist discourse and postdramatic theater to the transhistorically and culturally mediating power of Shakespeare as a means by which to discuss the affective impact of intermedial theater on today’s audiences.